Nuclear hormone receptors and female reproduction - Vattai, Aurelia; Fitzgerald, J. S.; Toth, Bettina; Markert, U. R.; Jeschke, U. (Current molecular medicine, 2013)
Background: Nuclear Hormone Receptors (NHR) are, as the name implies, receptors located in the cell nucleus that have transcription modulating characteristics. Activated non-steroidal lipophilic ligands bind these receptors resulting in dimerisation of the ligands, DNA-binding and transcriptional regulation of target proteins that influence especially cell differentiation, metabolic homeostasis and embryogenesis. - Methods: This review is based on publications derived from PubMed based pursuit of scientific literature in conjunction with the authors' experience. - Results: Here, a summary of NHR family members (RXR, PPAR, VDR, TR) first in respect to known general aspects such as ligands, binding domains, signalling mechanism and second focussing especially their influence on female reproduction is offered. Furthermore, crosstalk with other prominent signalling proteins important to trophoblast function [signal transducer and activator of transcription (STAT), mitogen-activated protein kinase (MAPK), nuclear factor 'kappa-light-chain-enhancer' of activated B-cells (NFκB), Akt/ phosphaidyl-3-kinase (PI3K), and Wnt, are described. - Conclusion: Considering their attributes, it is not surprising that NHR family members play a central role in female reproduction by targeting cell differentiation, metabolic homeostasis and embryogenesis. However, it seems that crosstalk depends on stage of trophoblast differentiation.